Effect of Rosa Roxburghii juice on starch digestibility: a focus on the binding of polyphenols to amylose and porcine pancreatic α-amylase by molecular modeling - Zhu, Jianzhong; Zhang, Bin; Tan, Chin Ping; Ding, Li; Shao, Miao; Chen, Chun; Fu, Xiong; Huang, Qiang (Elsevier, 2022)
Chestnut rose (Rosa Roxburghii) is an endemic fruit in China with many bioactivities. The present study investigated the effect of chestnut rose juice concentrate (CRJC) on the digestibility of normal wheat starch (NWS), with a focus on the interaction between polyphenols and amylose as well as that between polyphenols and porcine pancreatic α-amylase (PPA). NWS was mixed with CRJC and digestibility was determined using Englyst method. The composition of CRJC was analyzed by ultrahigh performance liquid chromatography-mass spectrometry. Molecular dynamics (MD) was used to study the binding between polyphenols and PPA and between polyphenols and amylose. The results showed that CRJC could significantly increase the resistant starch content. The MD results agreed with previous docking and experimental results regarding the inhibitory effects (IEs) of polyphenols (with galloyl and glycosyl group differences) against α-glucosidase. The MD results also showed that complex polyphenols with greater molecular weights or a high number of hydrogen bond donors (HBDs)/acceptors (HBAs) bind in a stronger and more lasting manner with amylose than simple polyphenols. CRJC has the potential to reduce the risk of developing type 2 diabetes and molecular simulation can be a supporting tool to study mechanisms in food system.